2021
DOI: 10.3390/molecules26051278
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations of Nicotinic Receptor α1 Subunit Reveal New Molecular Features of G153S Slow-Channel Myasthenia

Abstract: Slow-channel congenital myasthenic syndromes (SCCMSs) are rare genetic diseases caused by mutations in muscle nicotinic acetylcholine receptor (nAChR) subunits. Most of the known SCCMS-associated mutations localize at the transmembrane region near the ion pore. Only two SCCMS point mutations are at the extracellular domains near the acetylcholine binding site, α1(G153S) being one of them. In this work, a combination of molecular dynamics, targeted mutagenesis, fluorescent Ca2+ imaging and patch-clamp electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…SCCMS has been reported in 34 original articles since 1995 [ 27 , 31 , 162 , 163 , 165 , 168 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ]. As observed in other autosomal dominant disorders, the onset of SCCMS can be in adolescence or adulthood.…”
Section: Thirty-five Genes In 14 Groups Of Cmsmentioning
confidence: 99%
“…SCCMS has been reported in 34 original articles since 1995 [ 27 , 31 , 162 , 163 , 165 , 168 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ]. As observed in other autosomal dominant disorders, the onset of SCCMS can be in adolescence or adulthood.…”
Section: Thirty-five Genes In 14 Groups Of Cmsmentioning
confidence: 99%
“…It is also worth mentioning that some other marine alkaloids acting on nAChRs are now introduced not only as a valuable tool for fundamental research, but also as potential drugs. In our work, we have demonstrated that makaluvamine G from the marine sponge Zyzzia fuliginosa ( Figure 1 ) binds both to orthosteric and allosteric sites of the muscle-type nAChR ( Table 1 ) [ 91 ], thus being a perspective molecule for the design of allosteric drugs targeting these receptors, especially for treating slow-channel congenital myasthenic syndromes [ 92 ].…”
Section: Marine Low Molecular Weight Compounds Targeting Nachrsmentioning
confidence: 99%